Evaluation of the Salivary levels of TNF-α and IL35 in Iraqi patients with Rheumatoid Arthritis - Maher Abdulazeez Nsaif* 1, Heba Fadhil Hassan2 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The study examines the impact of TNF-α and IL35 levels in saliva on rheumatoid arthritis. It compares responder and non-responder patients, including 30 who responded to treatment and 30 who did not. The study found that rheumatoid arthritis incidence is three times higher in females than males. The age difference between RA patients and healthy controls was significant. TNF-α and IL35 levels were found to be highly significant in two patient groups compared to the control group. The study suggests that salivary TNF-α and IL35 levels can be used to study methotrexate effectiveness and disease activity.